EMAT (electromagnetic acoustic transducer) UT (ultrasonic testing) for thickness measurement and defect inspection on AM components - Lim, Ting Hui (Nanyang Technological University, 2023)
Additive manufacturing (AM) has reached widespread use in manufacturing industries in recent years. Defect inspection and geometric accuracy is critical in manufacturing for quality control. Ultrasonic testing (UT) is one of the best NDT methods used to detects flaws in AM products currently. EMAT is a way to perform UT which does not require contact with the test piece as compared to Piezoelectric Transducers. This project will use electromagnetic acoustic transducer (EMAT) to detect flaws in AM samples with rough surfaces. Conventional Piezoelectric Transducer was also used as a reference to compare the results obtained from using EMAT. AM samples were drilled with side-drilled holes (SDH) and flat-bottomed holes (FBH) which are common reference standards used in UT. Point pulse-echo testing were performed on the samples using both EMAT and Piezoelectric Transducer. The A-scans of the defects obtained were compared to evaluate the effectiveness of EMAT. EMAT is also useful for thickness measurement and was performed on a Rusted Sample with a rough surface. These measurements were then compared and evaluated. It was concluded that EMAT is more effective in both defect measurement and thickness measurement as compared to Piezoelectric Transducers, in terms of the signal-to-noise ratios and peak values.